If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 195 + -2x = 43x + 20 Reorder the terms: 195 + -2x = 20 + 43x Solving 195 + -2x = 20 + 43x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-43x' to each side of the equation. 195 + -2x + -43x = 20 + 43x + -43x Combine like terms: -2x + -43x = -45x 195 + -45x = 20 + 43x + -43x Combine like terms: 43x + -43x = 0 195 + -45x = 20 + 0 195 + -45x = 20 Add '-195' to each side of the equation. 195 + -195 + -45x = 20 + -195 Combine like terms: 195 + -195 = 0 0 + -45x = 20 + -195 -45x = 20 + -195 Combine like terms: 20 + -195 = -175 -45x = -175 Divide each side by '-45'. x = 3.888888889 Simplifying x = 3.888888889
| 3(x-2)+5=x-7 | | 4x-7x-13=3x+9-13 | | 7y+8-2y=6+4y+6 | | v/2=-2 | | v/=-2 | | 4x-7-13=-3x+9-13 | | 10x-4=5(2x+3) | | 3=1+y | | (6x-1)+(5x+3)=90 | | 3.8cm=10.4cm | | 11p+11q+p-4q-5p= | | 7t^4-10t^2-125= | | .5=.4y-.25 | | 8-2y=7 | | 2x^2+30=x^2+11x | | m-7=13 | | 7x-3(4-2x)= | | 54-3x=6x+15 | | -2x^2+13x+7= | | 21=10+x | | 13-8x=31-15x | | 0-a=10a-2 | | 8(3X+9)= | | -6-3= | | 6(5-x)+12x= | | 3x^3-10x^2+x+6=0 | | 3x+2x-20=35 | | 243x^5=1024 | | 9-2(x-4)= | | 70a^2b+99ab-9b= | | 5x-9=41 | | -6k=32 |